Analysis of Company Size and Profitability on Islamic Social Responsibility Disclosure - Sufiati, Sufiati; Pura, Rahman (Economics, Business, Accounting & Society Review, 2023)
The aim of this research is to analyze the determinants of Islamic Social Responsibility disclosure, namely company size and profitability. The research sample is 19 mining sub-sector companies listed on the Indonesian Sharia Stock Index (ISSI). Data were observed during 2019-2020 using the panel data technique, so that as many as 38 data were observed for analysis. Methods of data analysis with multiple regression analysis techniques. The results of the study show that company size has a significant positive effect on Islamic Social Responsibility, while profitability has no significant effect on Islamic Social Responsibility. Original research regarding CSR disclosure based on Islamic concepts in mining companies which are companies that carry out activities that are very sensitive to environmental pollution. Theoretical research implications regarding the development of CSR disclosure within the framework of the Islamic concept. Then practically it becomes a material consideration for company management to reveal Islamic Social Responsibility information